Study on biological value of different dietary inorganic phosphorus sources for broiler chickens - YIN Zhao-zheng; HONG Jian-wei; LI Xiao-liang; ZHU Chun-lei (浙江大学学报. 农业与生命科学版)
A grouped feeding trial, metabolism trial, and mensuration of bone and serum were made to determine biological value of different dietary inorganic phosphorus sources for broiler chickens. The results indicated that biological value of MCP、DCP、TCP、SP (each treated with four different levels of phosphorus addition, 0.06%, 0.12%, 0.18%, 0.24% respectively) were as follows, respectively: 100, 97,98,89 when body weight gain was employed as response criterion; 100,94,95.79 when ratio of phosphorus retention employed; 100,91,93,79 when bone ash content (the average of tibia ash and toe ash) employed; 100,92,93,77 when serum phosphorus level employed and 100,94,95,81 when average all above four criteria was used. It was suggested that MCP was the best dietary inorganic phosphorus source for broiler chickens, DCP and TCP were also ideal inorganic phosphorus sources with high efficiency, SP was a bad source of phosphorus for broiler chickens.